2022
DOI: 10.1093/ajcn/nqab428
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fat-reformulated dairy food consumption on postprandial flow-mediated dilatation and cardiometabolic risk biomarkers compared with conventional dairy: a randomized controlled trial

Abstract: Background Longer-term consumption of saturated fatty acid (SFA)-reduced, monounsaturated fatty acid (MUFA)-enriched dairy products have been reported to improve fasting flow-mediated vasodilation (FMD). Yet, their impact on endothelial function in the postprandial state warrants investigation. Objectives To compare the impact of a fatty acid (FA)-modified with a conventional (control) dairy diet on the postprandial %FMD (pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 43 publications
1
13
2
Order By: Relevance
“…In this context, unsaturated fats (USFAs) or structural lipids are attracting great attention with abundant essential fatty acids, and can lower cholesterol levels and prevent metabolic diseases. Meanwhile, it is indicated that dairy products modified with USFAs can effectively reduce the risk of cardiovascular disease (Vasilopoulou et al ., 2020; Markey et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, unsaturated fats (USFAs) or structural lipids are attracting great attention with abundant essential fatty acids, and can lower cholesterol levels and prevent metabolic diseases. Meanwhile, it is indicated that dairy products modified with USFAs can effectively reduce the risk of cardiovascular disease (Vasilopoulou et al ., 2020; Markey et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Supplementation of the dairy cow diet with plant oil or oilseeds is a reformulation initiative for partial replacement of milk SFAs with unsaturated fatty acids (FAs), primarily in the form of cis -MUFA [ 1 , 5 , 6 ]. In the REplacement of SaturatEd fat in dairy on Total cholesterol (RESET) study, we demonstrated that longer-term (12-wk) consumption of SFA-reduced, MUFA-enriched (FA-modified) milk, cheese and butter (∼ 41 g/day dairy fat) attenuated the rise in fasting serum LDL-cholesterol concentrations, enhanced endothelial-dependent flow-mediated dilatation (FMD) and plasma nitrite concentrations among a cohort of adults at moderate CVD risk, relative to conventional dairy products [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the REplacement of SaturatEd fat in dairy on Total cholesterol (RESET) study, we demonstrated that longer-term (12-wk) consumption of SFA-reduced, MUFA-enriched (FA-modified) milk, cheese and butter (∼ 41 g/day dairy fat) attenuated the rise in fasting serum LDL-cholesterol concentrations, enhanced endothelial-dependent flow-mediated dilatation (FMD) and plasma nitrite concentrations among a cohort of adults at moderate CVD risk, relative to conventional dairy products [ 1 ]. More recently, we presented evidence from the same ‘at risk’ cohort which indicated that longer-term intake of FA-modified dairy products, enhanced the postprandial (non-fasted) circulating apolipoprotein (apo)B response to representative sequential meals, but attenuated the %FMD response observed with the conventional dairy treatment [ 5 ]. In the context of dietary SFA replacement and cardiometabolic disease risk, this highlights the importance of considering biomarker assessment in the postprandial state [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations